The Competitive Determinants Strategy and its Impact on Competitive Advantage (Study of Solar Panel Industry in Indonesia) - Mappangara, Darman; Kartini, Dwi (International Review of Management and Marketing, 2019)
Several studies have reviewed New-Renewable Energy management, but very few studies focus on the study of Competitive Strategies and Competitive Advantages in the business of Renewable Photovoltaic Energy production. This study tries to fill the gap of the literature. This study uses the Structural Equation Modelling approach to data collected through questionnaires. Observations were made on the Directors who work in the company that focus on the management of Renewable Energy Photovoltaic in Indonesia. The results show that the development of competitive strategy is not influenced by external factors of the company. External factors also have no effect on competitive advantage either directly or indirectly. However, Product innovation plays a role in the formation of competitive strategies, and indirectly influences competitive advantage of Renewable Energy management company in Indonesia. Keywords: Competitive Strategy, Competitive Advantage, Renewable energy management JEL Classifications: L1, Q42 DOI: https://doi.org/10.32479/irmm.8115